PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP PRESTASI KERJA KARYAWAN PT PERKEBUNAN NUSANTARA XI SURABAYA - Nur Fadhilah, Yuliasri; Budi, Prabowo (Jurnal Bisnis Indonesia, 2021)
Human resources is one of the most important reasons which value andsupport the success of the company. This study is conducted to find out andanalyze The Actual Impact Of Motivation And Compensation To Employee'sAchievement Of  PT Perkebunan Nusantara XI SurabayaThis study is kind of descriptive and applied the quantitative researchmethod. Population is all employees with a sample amount of 70 respondents. Ituses multiple linear regression analysis techniques and research methods usingproportionate stratified random sampling technique.Based on the results of analysis in this study, there is a simultaneousimpact between motivation and compensation to employee's achievement withvalue F Count > F Table (24.051 > 3.13). 1 There is partial impact of motivationto employee's achievement with result T Count > T Table (6.819 > 1.996). 2Thereis partial impact of compensation to employee's achievement with value T Count> T Table (2.129 > 1.996). 3Keywords: Motivation, Compensation, Employee Achievement  DOI : https://doi.org/10.33005/jbi.v12i1.2597